Quality of life in patients with acne - Tadinac Babić, Meri (Array, 2001)
Acne can have a major impact on the quality of patients' lives, which can be measured using questionnaires that assess the health-related quality of life. However, earlier studies have established that the impairment is not related to the objective severity of acne. The aim of this study was to examine the quality of life in patients with acne and its relation to the self-rating and clinical rating of acne severity. Fourty-four patients with acne participated in the study. Acne severity was determined by a dermatologist, and the subjects were asked to self-rate their condition on a series of 5-point Likert scales. The quality of life was measured using Dermatology-Specific Quality of Life Questionnaire (DSQL), developed to evaluate the effects of skin disease on the specific forms of functioning and self-perception. The results showed a moderately lowered quality of life in patients with acne due to their disease, but the impairment depended less on the objective severity of acne and more on the patient’ s perception of his/her condition.